Evaluation of the Utilization of Health Operational Assistance on the Coverage of MCH Health Services at Community Health Centers in the Work Area of the Kupang City Health Office - Ervina Indriyani; Muntasir .; Yoseph Kenjam (Lontar : Journal of Community Health, 2023)
This study aims to determine the implementation of health operational assistance funds based on input, process, output, and outcome. This research is descriptive with a qualitative approach and narrative data analysis using univariate statistics. This research was conducted at the Health Centers of Oebobo, Sikumana, and Penfui. There were nine informants, namely the manager and the person in charge of the health operational assistance community health centers program. The study results describe that, in general, the inputs, processes, outputs, and outcomes have not gone well. Input disbursement of operational assistance funds is often late; Community health centers are also not competent in handling finances; there are multiple tasks outside of their competence, which increases the workload. In the process, the community health centers made POA, conducted mini-workshops, and conducted cross-program/cross-sector meetings but encountered problems implementing the MCH program and compiling SPJ reports. Output indicators of program success are still low; out of ten indicators, only two indicators reach the maximum percentage, namely, hands of obstetric complications handled at the community health centers (80%) and coverage of active family planning participants (70%). Outcome Health operational assistance funds can improve maternal and child health and help suppress MMR and IMR; from year to year, the cases have decreased even though the number is still far from the national average. It is recommended to have competent human resources in managing health operational assistance funds and the need for innovations so that program implementation can occur correctly in a pandemic.